A MADS-box gene-induced early flowering pear (Pyrus communis L.) for accelerated pear breeding - Tomes, Sumathi; Gunaseelan, Kularajathevan; Dragulescu, Monica; Wang, Yen-Yi; Guo, Lindy; Schaffer, Robert J.; Varkonyi-Gasic, Erika (Frontiers in Plant Science, 2023)
There have been a considerable number of studies that have successfully sped up the flowering cycle in woody perennial horticultural species. One particularly successful study in apple (Malus domestica) accelerated flowering using a silver birch (Betula pendula) APETALA1/FRUITFULL MADS-box gene BpMADS4, which yielded a good balance of vegetative growth to support subsequent flower and fruit development. In this study, BpMADS4 was constitutively expressed in European pear (Pyrus communis) to establish whether this could be used as a tool in a rapid pear breeding program. Transformed pear lines flowered within 6–18 months after grafting onto a quince (Cydonia oblonga) rootstock. Unlike the spindly habit of early flowering apples, the early flowering pear lines displayed a normal tree-like habit. Like apple, the flower appearance was normal, and the flowers were fertile, producing fruit and seed upon pollination. Seed from these transformed lines were germinated and 50% of the progeny flowered within 3 months of sowing, demonstrating a use for these in a fast breeding program.